2007
DOI: 10.1029/2006rs003581
|View full text |Cite
|
Sign up to set email alerts
|

Automatic scaling of critical frequency foF2 and MUF(3000)F2: A comparison between Autoscala and ARTIST 4.5 on Rome data

Abstract: [1] The performances of Autoscala and ARTIST 4.5 were comparatively evaluated using a large database of 6098 ionograms recorded from September 2005 to June 2006 by the digisonde DPS4 at the Rome ionospheric station. Results of comparisons between automatically and manually scaled data are shown for both programs highlighting the different behaviors. The Autoscala and ARTIST 4.5 values of foF2 and MUF(3000)F2 both agree with the hand-scaled values for $95% of ionograms. For the other $5% of ionograms, which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 10 publications
1
48
0
Order By: Relevance
“…The ionogram is memorized by Autoscala as two matrices A ord and A ext whose row and column numbers depend on the sounding settings as described in Pezzopane and Scotto (2007). The matrix element is an integer related to the echo amplitude received by the ionosonde, in decibels (dB) above the receiver sensitivity threshold.…”
Section: Autoscala and Data Inputmentioning
confidence: 99%
“…The ionogram is memorized by Autoscala as two matrices A ord and A ext whose row and column numbers depend on the sounding settings as described in Pezzopane and Scotto (2007). The matrix element is an integer related to the echo amplitude received by the ionosonde, in decibels (dB) above the receiver sensitivity threshold.…”
Section: Autoscala and Data Inputmentioning
confidence: 99%
“…The F2 layer identification performed by Autoscala (Pezzopane and Scotto, 2004) is not affected by characteristically flat Es multiple reflections, because the algorithm is designed to recognise the typical vertical asymptotical behaviour of the F2 traces (Pezzopane and Scotto, 2007). On the contrary Autoscala can be misled by multiple reflections from the F2 layer.…”
Section: Article In Pressmentioning
confidence: 99%
“…6, this automated analysis program erroneously perceived the echoes of the sporadic E-layer as the F2-layer, and incorrectly calculated foF2 and hmF2 of the F2-layer. Pezzopane & Scotto (2007) reported that when the highdensity sporadic E-layer occurred, the analysis program, Autoscala, did not calculate foF2 because the reflection trace of the F2-layer was uncertain due to the echoes of the sporadic E-layer, whereas the ARTIST 4.5 program calculated foF2 though the values were incorrect, which erroneously gave the results as if positive ionospheric disturbance occurred.…”
Section: Ionogram Analysismentioning
confidence: 99%